Simulating water table response to proposed changes in surface water management in the C-111 agricultural basin of south Florida - Kisekka, Isaya; Migliaccio, K. W.; Muñoz-Carpena, R.; Schaffer, B.; Boyer, T. H.; Li, Y. (My University, 2015)
As part of an effort to restore the hydrology of Everglades National Park (ENP), incremental raises in canal stage are proposed along a major canal draining south Florida called C-111, which separates ENP from agricultural lands. The study purpose was to use monitoring and modeling to investigate the effect of the proposed incremental raises in canal stage on water table elevation in agricultural lands. The objectives were to: (1) develop a MODFLOW based model for simulating groundwater flow within the study area, (2) apply the developed model to determine if the proposed changes in canal stage result in significant changes in water table elevation, root zone saturation or groundwater flooding and (3) assess aquifer response to large rainfall events. Results indicate the developed model was able to reproduce measured water table elevation with an average Nash-Sutcliffe > 0.9 and Root Mean Square Error < 0.05 m. The model predicted that incremental raises in canal stage resulted in significant differences (p < 0.05) in water table elevation. Increases in canal stage of 9 and 12 cm resulted in occasional root zone saturation of low elevation sites. The model was able to mimic the rise and fall of the water table pre and post Tropical Storm Isaac of August 2012. The model also predicted that lowering canal stage at least 48 hours prior to large storm (>2 year return period storm), reduced water table intrusion into the root zone. We conclude that the impact of operational changes in canal stage management on root zone saturation and groundwater flooding depended on micro-topography within the field and depth of storm events. The findings of this study can be used in fine tuning canal stage operations to minimize root zone saturation and groundwater flooding of agricultural fields while maximizing environmental benefits through increased water flow in the natural wetland areas. This study also highlights the benefit of detailed field scale simulations.
Keywords: Water table; Root zone; Groundwater flooding; MODFLOW; Canal-aquifer interactions